2019
DOI: 10.1521/jscp.2019.38.7.605
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Context: Social Connectedness Moderates Concurrent and Prospective Associations With Depressive Symptoms

Abstract: Introduction: Emotion regulation in healthy functioning and in depression is typically examined as an intrapersonal phenomenon, but growing evidence suggests social factors affect individuals' strategy use and effectiveness. We examined whether the role of emotion regulation in depression—concurrently and over four weeks—depends on social connectedness, predicting that higher social connectedness would dilute effects of one's own strategy use regardless of specific strategy. Methods: Young adult participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For example, stress can be downregulated by sharing negative news with other people (Lepore et al, 2000), while sharing positive news with people provides an opportunity for more positive events (Gable & Reis, 2010), and therefore more positive emotions and less stress (Lepore et al, 2000). Marroquín et al (2019) showed that social connections may moderate the relationship between emotion dysregulation and depression. Compared to those with fewer social connections, those with more social connections had weaker associations between experiential avoidance (difficulties accessing emotion regulation strategies) and depression scores suggesting that social connections helped buffer against negative impacts of depression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stress can be downregulated by sharing negative news with other people (Lepore et al, 2000), while sharing positive news with people provides an opportunity for more positive events (Gable & Reis, 2010), and therefore more positive emotions and less stress (Lepore et al, 2000). Marroquín et al (2019) showed that social connections may moderate the relationship between emotion dysregulation and depression. Compared to those with fewer social connections, those with more social connections had weaker associations between experiential avoidance (difficulties accessing emotion regulation strategies) and depression scores suggesting that social connections helped buffer against negative impacts of depression.…”
Section: Introductionmentioning
confidence: 99%